Predictors of Psychosis Remission in Psychotic Disorders That Co-occur With Substance Use - Caton, Carol L. M. (Oxford University Press, 2006)
Objective: To examine rates and predictors of psychosis remission at 1-year follow-up for emergency admissions diagnosed with primary psychotic disorders and substance-induced psychoses. Method: A total of 319 patients with comorbid psychosis and substance use, representing 83% of the original referred sample, were rediagnosed at 1 year postintake employing a research diagnostic assessment. Remission of psychosis was defined as the absence of positive and negative symptoms for at least 6 months. Likelihood ratio chi-square tests and multivariate logistic regression were the main means of analysis. Results: Of those with a baseline diagnosis of primary psychotic disorder, 50% were in remission at 1 year postintake, while of those with a baseline diagnosis of substance-induced psychosis, 77% were in remission at this time point. Lower Positive and Negative Syndrome Scale (PANSS) symptom levels at baseline, better premorbid functioning, greater insight into psychosis, and a shorter duration of untreated psychosis predicted remission at 1 year in both diagnostic groups. No interaction effects of baseline predictors and diagnosis type were observed. A stepwise multivariate logistic regression holding baseline diagnosis constant revealed the duration of untreated psychosis (odds ratio [OR] = 0.97; 95% confidence interval [CI] = 0.95, 0.997), total PANSS score (OR = 0.98; 95% CI = 0.97, 0.987), Premorbid Adjustment Scale score (OR = 0.13; 95% CI = 0.02, 0.88), and Scale to Assess Unawareness of Mental Disorders unawareness score (OR = 0.84; 95% CI = 0.71, 0.993) as key predictors of psychosis remission. Conclusions: The association of better premorbid adjustment, a shorter duration of untreated psychosis, better insight into psychotic symptoms, and lower severity of psychotic symptoms with improved clinical outcome, reported previously in studies of schizophrenia, generalizes to psychosis remission in psychotic disorders that are substance induced.